PENGARUH MATA KULIAH MICRO TEACHING DAN KEGIATAN PENGENALAN LINGKUNGAN PERSEKOLAHAN (PLP) TERHADAP KESIAPAN MENGAJAR MAHASISWA CALON GURU PADA FKIP UNIVERSITAS MAHADEWA INDONESIA TAHUN 2020 - Ni Luh Putu Cahayani (LP3M Universitas PGRI Mahadewa Indonesia, 2021)
The purpose of this study is to determine the effect of Micro Teaching Courses and Introduction to Schooling Environment (PLP)I on the Readiness of Prospective Teachers of FKIP Students, Universitas Mahadewa Indonesia in 2020. The data collection technique was carried out by distributing questionnaires or questionnaires based on the Likert Scale which was tested for validity and reliability. The data analysis used was product moment analysis, regression analysis of two predictors, and tested the significance of the F price. The results showed that there was an influence of the Micro Teaching Subject variable on the readiness of prospective teachers with correlation results, this was evidenced by the value of rcount 0.648> 0.165; there is an effect of Introduction to the School Environment on the Readiness of Prospective Teachers with correlation results, this is evidenced by the rcount value of 0.704> 0.165; there is a simultaneous influence of variables between the variables of Micro Teaching Courses and Introduction to the School Environment on the Readiness of Prospective Teachers. This is evidenced by Fcount 58.129 > Ftable 3.09. Results Relative contribution (SR) X1 37.2% and X2 62.8%. R Square 54.8% with X1 20.4% and X2 34.4%, the remaining 45.2% is influenced by other factors.